(untitled) (Journal of Veterinary Medicine and Animal Production, 2022)
In a study to detect T. lestoquardi infection using LAMP , 46 blood spots on filter paper were collected from adult apparently healthy Nubian goats of both sexes from several villages in Marawi area, Northern State, during May 2008. DNA was extracted from the blood spots using phenol chloroform method. Out of the 46 extracted DNA 36 (78.3%) were positive for T. lestoquardi infection using this technique.